(untitled) (Journal of Engineering, 2024)
Integrated project delivery is collaboratively applying the skills and knowledge of all participants to optimize the project’s results, increase owner value, decrease waste, and maximize efficiency during the design, fabrication, and construction processes. This study aims to determine IPD criteria positively impacting value engineering. To do this, the study has considered 9 main criteria according to PMP classification that already covers all project phases and 183 sub-criteria obtained from theoretical study and expert interviews (fieldwork). In this study, the SPSS (V26) program was used to analyze the main criteria and sub-criteria priorities from top to bottom according to their values of the Relative Importance Index. The results of this study have clarified the) Project stockholders Management ( as the most significant main criteria with RII (74%) and (Stakeholders, work team, customers, suppliers, and project managers’ support improve the probability of project implementation on the ground) as the most significant sub-criteria with (RII) (91%)